Etika Web Developer dalam Pendistribusian Pop-Up Ads pada Website - Ramdhani, Khusnun Najwa; Sari, Yuliana Mustika; Nafi', Raihan Muhammad; Firdaus Zahid, Ahmad Galvin; Fajariansyah, Ridwan; Arini, Florentina Yuni (Computer Science and Information Technology, 2024)
Globalization and the development of the internet have brought about major changes in the way information is obtained, including the use of pop-up ads as one of the increasingly popular digital marketing strategies. Pop-up ads are designed to attract users' attention with their flashy and interactive appearance. However, many users find these ads annoying as they often appear suddenly and repeatedly. In addition, pop-up ads may pose security risks in the form of malware, phishing, or malicious content that threatens users' personal data. This article analyzes the ethics of distributing pop-up ads on websites and highlights the important role of website developers in minimizing these potential risks. Through a literature review, this article asserts that website developers have a great responsibility in creating a safe, convenient, and user-oriented digital ecosystem. This includes regulating the frequency of ad appearances, creating attractive yet non-invasive designs, implementing ad due diligence, and safeguarding user privacy. By managing pop-up ads ethically, safely, and effectively, web developers can improve user experience, build trust, and prevent cybersecurity risks that harm all parties.